АНАЛІЗ ЧАСОВИХ РЯДІВ У ПРОГНОЗУВАННІ ФІНАНСОВИХ ІНВЕСТИЦІЙ - Лубенець, С. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
In the article the basic components of a highly probable forecast efficient financial investments based on the analysis of price time series with a simple trade and investment strategy Price action, proper risk management and investment capital, as well as the proper investment of thinking based on patience, discipline, and impartiality in making investment decisions.